Evaluasi Kesalahan Pelafalan Makhorijul Huruf Pada Siswa dalam Pembelajaran Tahfidz di MIS Al Ihsan - Rhevana Sekar Ayu; Afifah Nururrohmah; Muhammad Fadlan; Nursyahfira Nursyahfira; Hafizah Al Husna Anshori; Uswatun Hasanah; M. Ilmy Pramana; Mhd Helmi Lubis; Nikmah Royani Harahap; Tarigh Ayyub Lbs (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2026)
This community service activity aimed to evaluate and improve the quality of Al-Qur'an tahfidz learning at MIS Al-Ihsan. This approach focused on improving the articulation of Arabic letters by PPL students to enhance the fluency and accuracy of students' Al-Qur'an recitation. This study used a qualitative approach with a case study design to understand the types, causal factors, and impacts of pronunciation errors on the quality of students' Al-Qur'an memorization. Data was collected through participant observation, in-depth interviews, and analysis of learning documents, validated through data triangulation. The evaluation results showed serious difficulties in accurately pronouncing hijaiyah letters according to their makhraj, which can substantially alter the meaning of verses. Following guidance and pronunciation corrections, students showed enthusiasm and improvement in understanding the importance of makhārijul huruf. This activity provided valuable input for teachers and the institution to enhance tahfidz learning methods and curriculum design, and served as a valuable experience for PPL students in applying academic knowledge. Overall, this activity significantly contributed to improving the quality of Al-Qur'an tahfidz learning at MIS Al-Ihsan.